Forschungsmethodologie zum Wesen und Inhalt der beruflichen Identität der Hochschullehrkräfte - Spona, Ausma (International Dialogues on Education Journal, 2017)
Research on the development and self-realization of human personality is based on the perception of humans as philosophical beings. The question surrounding the „human being“ has become a question about the survival of humanity. In research centres in Europe, the USA, Canada, China, Australia the balance between biological, psyological and social components in human development is becoming an evermore active research focus. A research group from the Academy for Teacher Education and Educatioanl Administration Riga and the State University Smolensk (Russia) analyzed the professional identity of post-sendary teachers from two cultures with the aim of analyzing the nature of the professional identity of pedagogues and to determine a research methodology. Methodology in pedagogy involves teaching about the untiy of theory and research methods. The structure of scientific methodology is composed of four levels: 1) general theoretical, philosophical, methodological principles and approaches; 2) general pedagogical methodological principles; 3) regularities and principles of the sub-field of pedagogy; 4) principles of selection and use of research methodologies for a specific theme, based on empirical data. The methodological sources of this research are theoretical literature, dissertations in pedagogy as well as individual experiences of pedagogical and scientific activities. The research results show that the professional activity of post-secondary teachers and the quality of societal development influence and connect with each other.